(3CeGdj GdeMGedjs - (3GdeMGedj, GdVHj, CHh YHO Gddg, GdMSjf Hf ESeGYjd Hf eMeO Hf ESeGYjd, J (B330(3g`s
(3ChdgG (B:s
(3CNHQfG CHh GdZfGje eMeO Hf Ydj(B... (3bGd(B: (3UMHJ CHG GdOQOGA CJYde efg adeG MVQg GdehJ bGd(B...s
(3BNQgG (B:s
(3MOKfj GHf CHj ChjS bGd MOKfj CNj Yf SdjeGf Yf GHf YLdGf Yf YeQh Hf TYjH (B... (3Cf QShd Gddg Udi Gddg Ydjg hSde bGd(B: ... (3CMOG TjFG agh ddPj CYQg(B. (3BNQ GdLRA GdKGfjs
(3QhGjI(B: (3CHj eMeO YHO Gddg Hf YHjO Gddg Hf jMji Hf RcQjGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B2(3, U(B234s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs